Readministration of Cancer Drugs in a Patient with Chemorefractory Metastatic Colorectal Cancer. (23rd June 2020) - Kawagoe, Tetsuro; Ikeda, Go; Oshiro, Yu; Maruki, Yuta; Kaneko, Keiko; Iwakiri, Katsuhiko
Abstract : A 63-year-old woman was admitted to our institution for severe pain in her right lower abdomen caused by the perforation of cecal cancer. She underwent emergency surgery, from which she was diagnosed with cecal carcinoma with liver, lung, and lymph node metastases. As she was taking aspirin to prevent cerebral infarction, anti-vascular endothelial growth factor (receptor) antibody and regorafenib therapy were not used. Thus, we started a modified FOLFOX 6+cetuximab regimen. This first-line treatment initially achieved a partial response (PR), but she then developed progressive disease (PD) after 14 months. We changed the regimen to FOLFIRI, followed by trifluridine/tipiracil, but her progression-free survival periods were 2.7 months and 1 month, respectively. Although we cycled through the available array of standard cancer drugs, the patient showed a good performance status, and some benefit from treatment still seemed plausible. We readministered the 5-fluorouracil oral preparation S-1, which maintained stable disease (SD) for 7 months. After PD emerged, we readministered the anti-epidermal growth factor receptor (EGFR) antibody panitumumab for 7.5 months of SD. Finally, 39 months after her diagnosis, she died from rapidly progressing disease. However, her relatively long survival implies that readministering drugs similar to those used in previous regimens might benefit patients with metastatic colorectal cancer.